Identifying the Dimension of Entrepreneurial Ecosystem for Promoting Entrepreneurial Intention: A Study in Five Educational-Based Universities in Indonesia - Raya Sulistyowati; Angga Martha Mahendra; Farij Ibadil Maula; Septyan Budy Cahya; Putri Hestiningrum; Puspo Dewi Dirgantari; Yulita Pujiharti (Universitas Negeri Malang, 2023)
Entrepreneurship has been recognized among scholars and policy researchers as the driver of economic development. Many studies have identified the strategic role of higher education, especially business education, in increasing students' entrepreneurial intentions. However, the interest in entrepreneurship among students is insufficient. One of the causes of low interest in entrepreneurship among students is the internal or external environment, entrepreneurship learning, practical experience of entrepreneurship, and motivation for entrepreneurship. This study aims to identify the dimension of entrepreneurial ecosystem to promote entrepreneurial intention in several educational-based universities in Indonesia. Using the qualitative method, the findings indicated that each university may have different nuances in terms of developing an entrepreneurial ecosystem and its impact on students’ entrepreneurial intentions. The dimensions of entrepreneurial ecosystems identified in this research include entrepreneurial experience, institutional support, networks and connections, role models, entrepreneurial culture, and the entrepreneurial environment. Thus, it raises implications for the government and educational institutions to infiltrate the programs of other universities to promote entrepreneurial intention. Keywords: Entrepreneurial intention, Entrepreneurial ecosystem, Business intention, Educational-based university